Gloucester Cathedral
Further developments in vaulting occurred at Gloucester when the cloisters were rebuilt. The Norman Walls Were faced with paneling, new windows were inserted in each bay, and the entire structure was roofed with stone vaulting of new design. Integral ribs were incorporated in the panels which together form a series of inverted cones, or fans, springing from the piers.